Dynamic Compensation Contracts with Private Savings - He, Zhiguo (Review of Financial Studies, 2012)
This article studies a dynamic agency problem in which a risk-averse agent can save privately. In the optimal contract, (i) cash compensations exhibit downward rigidity to failures; (ii) permanent pay raises occur when the agent's historical performance is sufficiently good; (iii) and when the agent is dismissed due to poor performance, he walks away with severance pay to support his post-firing consumption at the current compensation level. Thus, the theory can simultaneously explain the popularity of options-like compensation contracts and the increasing incidence of forced turnovers with sizeable severance pay. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.